The Influence of Types of Extracurriculars and Discipline on Calculating Skills of Madrasah Tsanawiyah Almaarif 02 Singosari Students - Hidayati, Suci; Mustaghfiroh, Yuliana Nur; Sriharini (LP2M Institut Agama Islam Negeri (IAIN) Kediri, 2023)
This research originated from the problem of weak counting skills which affected the learning outcomes of MTs Almaarif 02 Singosari Malang students after the Covid-19 pandemic. The purpose of the research is to find out how much influence the type of extracurricular activities and discipline have onthecounting skills of MTs. Almaarif 02 Singosari Malang students for the 2021/2022 academic year. The method used in data analysis with logit regression with 50 studentsUSrespondents and counting skills as the main indicators. The results of the research of Model Rogistic Leggression obtained that the influence of extracurricular type and discipline is in the complete category which is mathematically modeled as follows:. To conclude thestudy resulted in a significant influence ofextracurricular typeon students' calculation skills by 0.0 08 smaller than the error rate of 5% while the disciplinary variable did not have a significant influence on the counting skills of MTs. Almaarif 02 students Singosari Malang.